Indapamide: a diuretic of choice for the treatment of hypertension? - Clarke, R (1991)
In recent years, the therapeutic approach to mild hypertension has evolved from a stepped care approach to one including varied, initial monotherapies, with the selection of drug based on factors present in an individual patient, followed by combination therapy. The greatest cumulative experience of the value of antihypertensive therapy has been obtained with diuretics. The reduction in risk of cardiovascular disease with successful antihypertensive therapy using conventional agents, including diuretics, is not as great as might have been anticipated by the magnitude of change in blood pressure. This could be due to antecedent cardiovascular injury prior to therapy or to risk factors induced by therapy. The recent introduction of a new generation of drugs with combined diuretic and hypotensive effects that reduce blood pressure without inducing the biochemical changes associated with thiazides, offers an opportunity to evaluate this question. Indapamide is the first of this new generation to be released. Its pharmacologic characteristics show that it has the prerequisites to be considered a first-line drug for use in hypertension. It meets the requirements of a Phase II or second generation drug in that it has similar efficacy, but less short term toxicity than first generation drugs. It has been introduced at a cost that is competitive with thiazides and potassium-sparing combination drugs and is cheaper than many other classes of antihypertensive drugs. The major caution in promoting its use is that its long term effect on morbidity and mortality in hypertensive disease has not yet been evaluated. In summary, this is a promising new drug that has the potential to replace first generation thiazides in the routine management of hypertension.